2023
DOI: 10.17503/agrivita.v45i2.3601
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Soil Cultivated with Durian (Durio zibethinus Murr.) in Gua Musang, Kelantan

Athirah Amran,
Mohd Rizal Ariffin,
Isharudin Md Isa
et al.

Abstract: This study was carried out in an area cultivated with durian in Gua Musang, Kelantan with a soil series of Rengam-Jerangau. The objective of this study was to determine the physicochemical properties of soil cultivated with durian at different elevations and samplings. The soil composite sampling was determined at three elevations (top, middle and bottom elevation) marked using GPS coordinate with two different depths (0-15 cm and 15-30 cm). The United States Department of Agriculture (USDA) of the soil textur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The pH value of soils was 4.5-5.0, which was extracted in distilled water with a ratio of soil/distilled water (1:2.5). According to Amran et al [28], who reported that durian thrives well in soil pH ranges from 5.5 to 6.5. Therefore, soil pH of the study locations was lower than that in optimal threshold of approximately 1.0 unit.…”
Section: Study Description Soil and Climatementioning
confidence: 99%
“…The pH value of soils was 4.5-5.0, which was extracted in distilled water with a ratio of soil/distilled water (1:2.5). According to Amran et al [28], who reported that durian thrives well in soil pH ranges from 5.5 to 6.5. Therefore, soil pH of the study locations was lower than that in optimal threshold of approximately 1.0 unit.…”
Section: Study Description Soil and Climatementioning
confidence: 99%
“…Warm temperatures is the best environment in for growth durians. The warmer climate aids the flower formation and fruiting process, which increases durian yields (Amran et al, 2023). The proper humidity helps durian plants thrive and enhances pollination, which is crucial for fruit formation.…”
Section: Discussionmentioning
confidence: 99%